Effect of chemical treatments to control enzymatic browning in minimal processed and packaged eggplant - R K , Harish Kumar; Alam, Tanweer; Khemariya , Priti (Journal of Postharvest Technology, 2018)
Minimal processing is a technique that is devised to preserve food as well as retain the nutritional quality and the sensory characteristics of the food product. This is done by reducing the reliance on heat as the main preservative action. To extend the shelf life of fruits and vegetables, this study is focused on developing a minimum processing packaging procedure with reduced undesired physicochemical reactions. In the present investigation shelf life of minimally processing studies on brinjal at different parameters and storage conditions has been carried out to control enzymatic browning.